On the Current State of Research in Czech Baroque Homiletics with Focus on Methodology (Past and Present Research;a Summary of Research Tasks and Issues) - Soleiman pour Hashemi, Michaela (Zagadnienia Rodzajów Literackich, 2023)
The study summarizes findings by Michaela Hashemi (Horáková) on homiletic texts of the early modern age, specifically the 17th century and the first half of the 18th century, with respect to the research context of the Czech environment. The article emphasizes the use of modern methods provided by literary theory which lead to relevant results. In the first part, the author presents a description of the history and the present of domestic homiletic research; the second part defines the key terms — Baroque homiletic texts and the exemplum (conceived as a homiletic intertext). The third part concentrates on other individual research tasks and issues relating to them, first in research of homiletic text production in a single historically conceived area (specifically texts with the Cyril and Methodius theme) and then territories of several different areas of the given period (from the end of the 17th to mid-18th century) in cultural contact (the Nepomucene theme). The following sections discuss the so-called topos of the dimension of Baroque mysticism (across Baroque literature genres, in texts of both higher and lower styles). The conclusion summarizes the finding that the study of homiletic texts employs classic methods (historical and philological) alongside modern ones, primarily the concept of everyday life and intertextuality.